The relationship between red cell distribution width and all-cause and cause-specific mortality in a general population - Pan, Jingxue (Sci Rep, 2019)
Red Cell Distribution Width (RDW) could be a risk factor for developing various chronic diseases, and seems to be a prognostic marker in patients with cardiovascular disease (CVD) or cancer. Our aim was to explore the association between RDW and all-cause and cause-specific mortality in a general population. RDW was measured in 27,063 participants (aged 45–73 years) from the population-based Malmö Diet and Cancer cohort. After a follow-up of 19.8 ± 5.5 years, Cox proportional hazards regression analysis was used to study the relationship between RDW and all-cause and cause-specific mortality, with adjustment for confounding factors. A total of 9388 individuals (4715 men and 4673 women) died during the follow up. High RDW was significantly associated with all-cause mortality (HR, 4(th) vs. 1(st) quartile: 1.34, 95%CI: 1.24–1.45), cancer mortality (HR: 1.27, 95%CI: 1.12–1.44), CVD mortality (HR: 1.39, 95%CI: 1.21–1.59), and respiratory disease mortality (HR: 1.47, 95%CI: 1.06–2.03). The C-statistic increased significantly from 0.732 to 0.737 when adding RDW to a model adjusted for age and sex. There was a significant interaction between RDW and BMI with respect to all-cause mortality. We concluded that RDW is associated with mortality and propose that high RDW is a significant, but non-specific marker of mortality risk in the general population.